2020
DOI: 10.1096/fj.202000766r
|View full text |Cite
|
Sign up to set email alerts
|

The impact of umbilical vein blood flow and glucose concentration on blood flow distribution to the fetal liver and systemic organs in healthy pregnancies

Abstract: Glucose is a major energy substrate for the fetus, including liver, heart, and brain metabolism. The umbilical vein (UV) blood flow supplies the fetal liver directly from the placenta, whereas a fraction is shunted via ductus venosus (DV) to the fetal systemic circulation bypassing the fetal liver. We hypothesized UV glucose concentration to be a major regulator of the distribution of glucose supply between the fetal liver and DV, and explored the influence of maternal metabolic status on this distribution. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
0
9
0
1
Order By: Relevance
“…Overall, the analyzed research papers point out a possible connection between fetal liver indices and GDM; however, the base of evidence is too small to conclude that these parameters can serve as predictors of GDM in pregnancy. Consequently, further research is needed to clarify the relationship between fetal liver indices and GDM and, if our hypothesis is confirmed, to delineate cutoff values for the variables that could predict the development of GDM [5,24,37,68,69,[85][86][87][88][89][90][91][92][93]. Only one study, conducted by Perovic et al (2014), proposed an FLL of 39 mm as a predictor of GDM [37].…”
Section: Fetal Liver Length Measurements By Ultrasound-any Value?mentioning
confidence: 86%
See 1 more Smart Citation
“…Overall, the analyzed research papers point out a possible connection between fetal liver indices and GDM; however, the base of evidence is too small to conclude that these parameters can serve as predictors of GDM in pregnancy. Consequently, further research is needed to clarify the relationship between fetal liver indices and GDM and, if our hypothesis is confirmed, to delineate cutoff values for the variables that could predict the development of GDM [5,24,37,68,69,[85][86][87][88][89][90][91][92][93]. Only one study, conducted by Perovic et al (2014), proposed an FLL of 39 mm as a predictor of GDM [37].…”
Section: Fetal Liver Length Measurements By Ultrasound-any Value?mentioning
confidence: 86%
“…In the analyzed papers, the most investigated fetal liver indices were FLL (n = 5) and FLV (n = 5). Overall, the subjects with GDM had higher FLL and FLV versus comparators, with several studies revealing associations between FLL and (or) FLV and anthropometric (BMI or BW in particular) or carbohydrate metabolism indices (FPG or HbA1c) [5,24,37,68,69,[85][86][87][88][89][90][91][92][93]. Interestingly, Boito et al (2007) demonstrated that if glycemia is adequately controlled and if GDM is appropriately treated, the FLV is similar between GDM and NGT pregnancies [86].…”
Section: Fetal Liver Length Measurements By Ultrasound-any Value?mentioning
confidence: 99%
“…The maternal metabolic status seems to influence the fetal response to a maternal meal: in a healthy population, increased umbilical flow to liver was observed in normal weight, but not in overweight mothers [ 17 ]. Further, the maternal-fetal glucose gradient correlated negatively with umbilical flow to liver in pregnancies of normal weight, but not overweight women [ 18 ]. Inadequate glycemic control is more frequent in patients with type 1 diabetes with high BMI [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of the umbilical blood is influenced by maternal BMI in pregnancies without diabetes [ 17 ]. In normal weight women the maternal-fetal glucose gradient was found to correlate with the distribution of the umbilical flow to the fetal liver, while in overweight mothers no such correlation was found [ 18 ]. In pregnancies with PGDM, we found that the proportion of umbilical venous return distributed to the fetal liver was graded according to maternal HbA 1C [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted investigating the association between fetal liver blood flow volume and maternal pregravid BMI (62), gestational weight gain (63), serum glucose level (64)(65)(66), and fetal growth restriction (67). More recent report showed the correlation between fetal liver blood flow volume and placental corticotrophin releasing hormone, which is a paracrine determinant of the placental vasculature (68).…”
Section: Fetal Liver Blood Flow Volume and Infant Body Compositionmentioning
confidence: 99%